A dramaturgia de títeres de Federico García Lorca: entre o culto e o popular (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
O objetivo do presente estudo é realizar uma pequena análise dos aspectosligados à dramaturgia de títeres de Federico García Lorca. Para tanto, escolhemos dois textos que nos parecem exemplares dessa dramaturgia: La Niña que riega la albahaca y el Príncipe preguntón e La tragicomedia de don Cristóbal y la seña Rosita. São textos que, embora possuam características híbridas, trazem elementos que podem classificá-los entre o culto e o popular.Palavras-chave: García Lorca; dramaturgia; títeres. Abstract: This study conducts a short analysis of factors related to the puppet theatre of Federico García Lorca. We have chosen two texts that we consider to be examples of this dramaturgy: La Niña que riega la albahaca and the Príncipe preguntón and La tragicomedia de don Cristóbal y la seña Rosita. Despite the hybrid characteristics of these works, they present elements that allow classifying them between popular and erudite.Keywords: García Lorca; dramaturgy; puppets.